2007
DOI: 10.1186/1471-2164-8-390
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis by SAGE reveals new mechanisms of v-erbA oncogene action

Abstract: Background: The v-erbA oncogene, carried by the Avian Erythroblastosis Virus, derives from the c-erbAα proto-oncogene that encodes the nuclear receptor for triiodothyronine (T3R). v-ErbA transforms erythroid progenitors in vitro by blocking their differentiation, supposedly by interference with T3R and RAR (Retinoic Acid Receptor). However, v-ErbA target genes involved in its transforming activity still remain to be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…The variability observed here is well known in our cell model and it was highlighted in other publications from our laboratory. 13 We suspect it might very well be related to the known stochasticity in gene expression, 18 reinforced by T2ECs being primary cells, stemming from different bone marrow extractions.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…The variability observed here is well known in our cell model and it was highlighted in other publications from our laboratory. 13 We suspect it might very well be related to the known stochasticity in gene expression, 18 reinforced by T2ECs being primary cells, stemming from different bone marrow extractions.…”
Section: Introductionmentioning
confidence: 98%
“…10 Hence, v-erbA was thought to act as a negative-dominant mutant of thyroid hormone triiodothyronine and retinoic acid receptor, 11,12 although we have recently demonstrated that the majority of v-erbA target genes were neither T3 nor retinoic acid-target genes. 13 Moreover, the subcellular localization of v-erbA is different from that of c-erbAa1, which also confers on v-erbA other mechanisms of action. 13,14 Our previous works demonstrated that some of these mechanisms were related to the alteration of the mTOR and TGF-b signal transduction pathways in erythroid progenitors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations